2019
DOI: 10.4103/ijo.ijo_799_18
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography features of retinitis post-rickettsial fever

Abstract: The intraocular manifestations of rickettisial retinitis include retinal vasculitis, maculopathy, optic neuritis, and neurosensory detachment. Extensive leakage of dye on the fundus fluorescein angiography may obscure visualization in eyes with retinitis. We report the vascular changes in eyes with rickettsial retinitis and its response to treatment using optical coherence tomography angiography. The microvascular abnormalities we noted were, capillary drop out areas corresponding to retinitis patches, vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Our series did not show any individual MAs on OCTA. The CC slabs showed signal void areas which can be attributed to shadowing caused by the overlying retinitis patch similar that reported by Shanmugam et al 22 The regular vascular pattern or the “angio-architecture” in SCP and DCP was lost in active retinitis, the intraretinal edema and exudation causing an impression of vessel drop out. The flow void areas in the choriocapillaris layer are due to the shadow effect of the superficial edema on to the choroid resulting in loss of the regular coarse architecture.…”
Section: Discussionsupporting
confidence: 83%
“…Our series did not show any individual MAs on OCTA. The CC slabs showed signal void areas which can be attributed to shadowing caused by the overlying retinitis patch similar that reported by Shanmugam et al 22 The regular vascular pattern or the “angio-architecture” in SCP and DCP was lost in active retinitis, the intraretinal edema and exudation causing an impression of vessel drop out. The flow void areas in the choriocapillaris layer are due to the shadow effect of the superficial edema on to the choroid resulting in loss of the regular coarse architecture.…”
Section: Discussionsupporting
confidence: 83%
“…Shanmugam et al . [ 9 ] and Kalhoun et al .,[ 4 ] also showed that it is difficult to discern the perfusion status in the initial OCTA scans due to acute inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A case of posterior focal retinitis in a cohort was found to be positive with non-ST RDs using WFT [ 72 ]. Few case reports of retinitis using WFT were documented [ 73 , 74 ]. A case of bilateral anterior uveitis with retinitis was documented with positive WFT for both OX-2 and OX-19 [ 75 ].…”
Section: Resultsmentioning
confidence: 99%